Child Care Policy as an Anti-Poverty Strategy: The Need to Address Neurophysiological Self-Regulation. (October 2021) - Holochwost, Steven J.; Gomes, Lindsay A.; Propper, Cathi B.; Brown, Eleanor D.; Iruka, Iheoma U.
High-quality early care and education can mitigate the short- and long-term effects of poverty on young children's development. Therefore, policies that expand access to high-quality early care and education can be an effective anti-poverty strategy. A number of programs demonstrably foster volitional processes of self-regulation—the capacity to control emotions, thoughts, and behaviors—among young children in poverty. However, relatively little is known about how the activity of the neurophysiological systems that form the interface between brain and body supports these processes of self-regulation in early care and education settings. Maximizing the efficacy of early care and education as an anti-poverty strategy requires adopting policies to advance three interrelated goals: understanding, accommodating, and reconfiguring young children's neurophysiological function in the early care and education environment.